The physiological effects of swimming competition on 16-17-year-old elite female swimmers - Griffin, A. J.; Unnithan, V. B.; Ridges, P. (Pediatric Exercise Science, 1999)
The purpose of this study was to assess the effects of a weekend of swimming competition on various physiological parameters in a group of elite female swimmers. The results suggest that swimming competition causes a number of the recognized symptoms related to excitatory (acute) overtraining